21-Day dermal exposure to aircraft engine oils: effects on esterase activities in brain and liver tissues, blood, plasma, and clinical chemistry parameters for Sprague Dawley rats. Issue 9 (3rd May 2021) - Sibomana, Isaie; Rohan, Joyce G.; Mattie, David R.
ABSTRACT: This dermal study tested the potential toxicity of grade 3 (G3) and 4 (G4) organophosphate-containing aircraft engine oils in both new (G3-N, G4-N) and used states (G3-U, G4-U) to alter esterase activities in blood, brain and liver tissues, clinical chemistry parameters, and electrophysiology of hippocampal neurons. A 300 µl volume of undiluted oil was applied in Hill Top Chamber Systems®, then attached to fur-free test sites on backs of male and female Sprague Dawley rats for 6 hr/day, 5 days/week for 21 days. Recovery rats received similar treatments and kept for 14 days post-exposure to screen for reversibility, persistence, or delayed occurrence of toxicity. In brain, both versions of G3 and G4 significantly decreased (32–41%) female acetylcholinesterase (AChE) activity while in males only G3-N and G4-N reduced (33%) AChE activity. Oils did not markedly affect AChE in liver, regardless of gender. In whole blood, G3-U decreased female AChE (29%) which persisted during recovery (32%). G4-N significantly lowered (29%) butyrylcholinesterase (BChE) in male plasma, but this effect was resolved during recovery. For clinical chemistry indices, only globulin levels in female plasma significantly increased following G3-N or G4-N exposure. Preliminary electrophysiology data suggested that effects of both versions of G3 and G4 on hippocampal function may be gender dependent. Aircraft maintenance workers may be at risk if precautions are not taken to minimize long-term aircraft oil exposure.